Pemberdayaan Peserta Didik dalam Pengembangan E-Commerce melalui Strategi Transformasi Wirausaha Digital di MA Islmiyah Senori - Zeni Faridah; Siti Maftuhah; Muhammad Abdul Mujib (Journal of Innovation and Contribution to Community Service, 2025)
Creative endeavors are very important, especially for the younger generation. However, for many young people in the digital era, technological skills to market and develop creative businesses have become very important, especially for the younger generation. However, many young people at the madrasah level do not yet have an understanding of digital technology-based entrepreneurship. The creative young entrepreneur training program at MA Islamiyah Senori aims to provide practical skills in utilizing digital technology, especially in marketing via social media, creating creative content, and managing online businesses. The method used is Participatory Action Research (PAR) which actively involves students through direct practice, digital business simulations, and personal mentoring for 3 months. The results of the training show an increase in students' skills in utilizing social media for business, creating creative content, and managing digital-based businesses. Some students have started their own businesses and market products through e-commerce platforms. Apart from that, this training also increases students' motivation to become entrepreneurs and develop more concrete business plans. It is hoped that this program can help create creative and innovative young entrepreneurs, as well as contribute to the development of the digital economy in Indonesia.